p = (3/2)^x
p - 1/p = 1
p² - p - 1 = 0
p = (1 +√5) / 2
(3/2)^x = (1 +√5) / 2
x ln (3/2) = ln ((1 +√5)/2)
Answer:
x = ln((1 + √5)/2) / ln(3/2) =1.1868143902809817175449880
2007-04-03 08:36:08
·
answer #1
·
answered by Alexander 6
·
0⤊
0⤋
When all else fails, try a little t&e (trial and error)
Actually at x=1, you're not too far away from an answer, so try somthing around x=4/3. You can also do this with logs (remember that the log(2/3) is a negative number. )
2007-04-03 15:28:35
·
answer #2
·
answered by cattbarf 7
·
0⤊
0⤋
x = [lg (1 + â5) - 1] / [lg 3 - 1] â 1.187
(lg means log base 2)
Let A = (3/2)^x, so
A - A⁻¹ = 1
A² - 1 = A
A² - A - 1 = 0
A = (1 ± â[(-1)² - 4(1)(-1)])/2(1)
A = ½(1 ± â5)
(3/2)^x = ½(1 ± â5)
x lg [3/2] = lg [½(1 ± â5)]
x = lg[½(1 ± â5)] / lg[3/2]
x = [lg (1 ± â5) - lg 2] / [lg 3 - ln 2]
x = [lg (1 ± â5) - 1] / [lg 3 - 1]
We can discount the minus if the answer is to be real, since 1 - â5 is negative, and the lg of a negative number is undefined over the real numbers.
2007-04-03 15:32:37
·
answer #3
·
answered by Phred 3
·
0⤊
0⤋
Let y = (3/2)^x... then
y - 1/y = 1
â y = phi or y=-1/phi where phi is the Golden Ratio
Solution 1: y = (3/2)^x = phi
â x = log phi / (log 3 - log 2)
Solution 2: y = (3/2)^x = -1/phi doesn't work because
LHS > 0 > RHS.
2007-04-03 15:51:19
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋